2003
DOI: 10.4049/jimmunol.171.9.4853
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Vascular Endothelial Growth Factor Receptor I (VEGF-RI), but not VEGF-RII, Suppresses Joint Destruction in the K/BxN Model of Rheumatoid Arthritis

Abstract: It was recently shown that vascular endothelial growth factor (VEGF), a growth factor for endothelial cells, plays a pivotal role in rheumatoid arthritis. VEGF binds to specific receptors, known as VEGF-RI and VEGF-RII. We assessed the physical and histological effects of selective blockade of VEGF and its receptors in transgenic K/BxN mice, a model of rheumatoid arthritis very close to the human disease. Mice were treated with anti-mouse VEGF Ab, anti-mouse VEGF-RI and -RII Abs, and an inhibitor of VEGF-RI ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 31 publications
8
86
0
1
Order By: Relevance
“…Other receptors involved in angiogenesis, such as Tie receptors and their ligands, the angiopoietins, are known to be expressed in synovial membrane from RA patients and are regulated by TNF␣ (27). In addition, it is known that soluble chimeric VEGFR-1 protein abrogates angiogenesis in RA (28), while blockade of VEGFR-1, but not VEGFR-2, was shown to be beneficial in a transgenic mouse model of RA (29). Matrix metalloproteinases such as ADAMS have been found to be involved directly in the cleavage of extra (8).…”
Section: Discussionmentioning
confidence: 99%
“…Other receptors involved in angiogenesis, such as Tie receptors and their ligands, the angiopoietins, are known to be expressed in synovial membrane from RA patients and are regulated by TNF␣ (27). In addition, it is known that soluble chimeric VEGFR-1 protein abrogates angiogenesis in RA (28), while blockade of VEGFR-1, but not VEGFR-2, was shown to be beneficial in a transgenic mouse model of RA (29). Matrix metalloproteinases such as ADAMS have been found to be involved directly in the cleavage of extra (8).…”
Section: Discussionmentioning
confidence: 99%
“…51 It is believed that VEGF plays a central role in pannus development and thus administration of specific inhibitors of the VEGF-RI pathway suppresses arthritis and prevents bone destruction in experimental arthritis. 52 It has been demonstrated that HO-1 activity can be related to angiogenesis. Thus, this enzyme has been shown to induce VEGF in cultured endothelial cells by an increased transcription likely dependent on CO generated by HO-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), the most powerful angiogenic molecule, is associated with various physiological and pathological neovascularization, including synovial angiogenesis in RA [3]. In RA, VEGF is strongly expressed by synovial macrophages, fibroblasts surrounding microvessels, vascular smooth muscle cells, and synovial lining cells [4,5]. VEGF expression begins very early and it also persists throughout the disease course [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In RA, VEGF is strongly expressed by synovial macrophages, fibroblasts surrounding microvessels, vascular smooth muscle cells, and synovial lining cells [4,5]. VEGF expression begins very early and it also persists throughout the disease course [4,5]. VEGF binds two types of receptors: vascular endothelial growth factor receptor I (VEGF RI) and vascular endothelial growth factor receptor II (VEGF RII) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation